2001
DOI: 10.1021/jf0001031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Treatments on the Evolution of Polyamines during Refrigerated Storage of Eggplants

Abstract: The applicability of a thermal treatment was compared with modified-atmosphere (MA) storage in relation to chilling injury (CI) and polyamines evolution in eggplants. Fruits underwent physiological disorders at 3 degrees C, evidenced by the appearance of surface injuries at the third day of storage, and, after moving the fruits to 20 degrees C, by increased respiratory activity and more intense ethylene production. Storage of fruits in sealed low-density polyethylene bags and a previous treatment with heated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
0
28
0
2
Order By: Relevance
“…Data obtained from different studies reflect this variation. Using different techniques for measuring polyamines, in addition to the other influencing factors such as storage periods and conditions as well as cooking method, might also play a role in affecting the resulting database (5, 57). These different analytical methods showed some variation in polyamine contents in the same type of food.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained from different studies reflect this variation. Using different techniques for measuring polyamines, in addition to the other influencing factors such as storage periods and conditions as well as cooking method, might also play a role in affecting the resulting database (5, 57). These different analytical methods showed some variation in polyamine contents in the same type of food.…”
Section: Discussionmentioning
confidence: 99%
“…113 -115 Andersen and Kent 116,117 found that increases in the content of ACC, the immediate precursor of ethylene, and ethylene production in cucumbers occurred immediately after their transference to room temperature. Usually, the development of CI symptoms occurs when the fruits are reconditioned at room temperature after cold storage, and this is correlated with a sharp increase in ethylene production, as has been observed in many different fruits such as cantaloupe melon, 80 mango, 114 pear, 118 zucchini 119 and eggplant 120 and in different citrus fruits such as mandarin, orange 121 and grapefruit. 122 This increased ethylene production can be interpreted in two different ways, either (i) as a simple response to low temperatures or (ii) that this ripening and senescence hormone could induce CI in sensitive species.…”
Section: The Role Of Ethylene In the Stimulation Of CI And The Influementioning
confidence: 94%
“…Refrigeration is one of the most effective methods of preserving the quality of many fruits and vegetables for several days [32,50]. Low temperature storage can protect nonappearance quality attributes like texture, nutrition, aroma, and flavour in many harvested fruits [51].…”
Section: Refrigeration Storagementioning
confidence: 99%
“…It is one of the approaches that can be used to avoid or reduce chilling injuries in stored fruits [57]. Postharvest heat treatments using hot air and heated water have been reported to reduce chilling injuries in fruits like mangoes, oranges, zucchini, and tomatoes [50]. Heat treating of tomato fruit at temperatures of about 37-42 ∘ C prior to cold storage can slow down ripening whilst increasing pathogenic resistance when in storage [58].…”
Section: Postharvest Heat Treatment Of Tomatoesmentioning
confidence: 99%